Pollen and spores records of lake sediments from the Eifel, Germany - Frank Sirocko; Johannes Albert; Sarah Britzius; Frank Dreher; Alfredo Martínez-García; Anthony Dosseto; Joachim Burger; Thomas Terberger; Gerald H Haug (PANGAEA, 2025)
In order to reconstruct the presence of Megafauna in relation to vegetation cover in Central Europe, a total of 250 pollen samples and 203 samples for spores of the coprophilous fungi Sporormiella and Sordaria were analyzed. The results are accompanied by measurements of δ7Li and n-alkanes. Samples derive from composite drill cores from Holzmaar and Auel infilled maar and cover the last 60,000 years. This work is part of the ELSA project.